ANALISIS KEPATUHAN HUKUM PRESIDEN DAN DPR ATAS PUTUSAN MAHKAMAH KONSTITUSI DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Sheyka Tsana’a Allifa; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The Constitutional Court is a judicial institution that exercises independentjudicial power to administer justice to uphold law and justice. After makingamendments to the Undang-Undang Dasar 1945, a Constitutional Court wasformed which was needed to balance the powers of the DPR and the President interms of making laws. One of the powers possessed by the Constitutional Court isto conduct a judicial review of the Undang-Undang Dasar 1945 Constitution orthe so-called Judicial Review. In this case, the Constitutional Court will examinethe petition for the existence of people's constitutional rights that have beenviolated, with a final and binding decision. However, in implementing itsdecisions, the Constitutional Court does not have a special apparatus to overseethe assurance that decisions are implemented by the addreesat institution, namelythe President and the DPR. This has resulted in many decisions that have not beenfollowed up, or the inappropriate follow-up by the President and the DPR.disobedience to the decision of the Constitutional Court is tantamount todisobedience to the Undang-Undang Dasar 1945 Constitution which is the sourceof the Constitutional Court in examining the law.This research will be structured using the type of normative juridicalresearch, namely research that is focused on examining the application of legalrules or norms to legal principles and theories. The data collection technique usedin this research is literature study. The approach used in this research is to use anormative approach, namely library law research.The results of the research conducted by the author are, first, theconditional decision issued by the Constitutional Court is intended for law-forming institutions to have a direction to follow up on the decision. With thisconditional decision does not need to be followed up. Second, Impeachment is away to limit the President in exercising his authority. Impeachment which is aform of responsibility of the President in carrying out legal provisions.Impeachment efforts can be used to strengthen the implementation of the follow-up to the decisions of the Constitutional Court which are presented in the AnnualSession of the MPR.Keyword : Noncompliance – Constitutional Court Decision – President andDPR